Fierce invalids home from hot climates - Robbins, Tom (New York : Bantam Books, 2000)
No one else writes like Tom Robbins. But thank goodness he does. Not only does he tell a ripping good yarn, but the language he uses shows you that he obviously takes the time to chew and taste each sentence thoroughly. He is in love with words, and it shows on every page. He takes an ordinary scene and makes you see it in a completely new way. For instance, he describes a sunset as the sun dropping like a gold coin into a slot and ocean biting the coin to make sure it is really gold. And you can actually SEE it right along with him. It's so damned, as Switters calls South America, "VIVID."
Keywords: Intelligence officers -- Fiction; Adventure Fiction; Adventure fiction; Satire